Kültürel Coğrafya - Kayserili, Alperen; Sakaoğlu, Emre; Öcal, Tülay; Şen, Ömer; Şahinalp, Mehmet Sait; Zaman, Nilgün; Doğmuş, Özge Can; Alkan, Adnan; Göközkut, Burcu; Toroğlu, Emin; Vural, Ercan; Kara, Hasan; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-